The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/jper.20-0315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the need to prescribe opioid medication to control post‐surgical pain of different periodontal/oral surgeries

Abstract: Background: To determine the level of perceived pain after different types of periodontal/oral surgical procedures, and the differences in patients' selection of pain management, over the counter (OTC) versus opioid, based on procedure type. Methods: Patients undergoing surgical procedures were asked to complete a pain questionnaire at four time points: 1) before surgery 2) first dose of analgesic at home, 3) 24 hours postoperatively, and 4) 72 hours postoperatively. The questionnaire consisted of numerical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…With this increased awareness at the predoctoral level, awareness increased throughout all the faculty to include part-time faculty at CUSDM. In addition, verbal dissemination of the results from the Graduate Periodontics self-reported questionnaire for postoperative pain study which demonstrated that the majority of periodontal/oral surgeries do not need a postsurgical opioid pain prescription 27 had an impact on prescribing habits. Review of the prescribing trends in 2019 showed another drop.…”
Section: Resultsmentioning
confidence: 99%
“…With this increased awareness at the predoctoral level, awareness increased throughout all the faculty to include part-time faculty at CUSDM. In addition, verbal dissemination of the results from the Graduate Periodontics self-reported questionnaire for postoperative pain study which demonstrated that the majority of periodontal/oral surgeries do not need a postsurgical opioid pain prescription 27 had an impact on prescribing habits. Review of the prescribing trends in 2019 showed another drop.…”
Section: Resultsmentioning
confidence: 99%
“…One reason for this relationship is that instrumentation becomes more difficult in deeper pockets due to poor access, decreased curette efficiency, and complex root anatomy 13,14 . Surgical access allows more effective calculus removal 12 ; however, conventional approaches are often associated with post‐operative discomfort, gingival recession, and tooth sensitivity 15,16 . Minimally invasive surgery (MIS) techniques, with limited incisions and flap access, have been developed to mitigate these potential side effects, but visualization of root surfaces can be difficult 17 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Surgical access allows more effective calculus removal 12 ; however, conventional approaches are often associated with post-operative discomfort, gingival recession, and tooth sensitivity. 15,16 Minimally invasive surgery (MIS) techniques, with limited incisions and flap access, have been developed to mitigate these potential side effects, but visualization of root surfaces can be difficult. 17 Aids including surgical telescopes, surgical microscopes, and glass fiber endoscopes have been used to improve visualization in MIS, though each of these aids has been associated with difficulties of either access, magnification, or blurred imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is greater concern for adverse events and drug interactions in this population. The pain intensity level following implant placement is generally less than dental impaction surgery ( Al-Khabbaz et al, 2007 ; Al-Bayati et al, 2021 ), so over-the-counter (OTC) doses of NSAIDs and/or acetaminophen are an option for pain management in these patients. OTC dosing is more conservative than prescription dosing mainly for safety reasons ( Hersh et al, 2007 ), and these lower dosages along with the shorter maximum durations of use (no more than 10-day) contribute to a side-effect profile no different from placebo ( DeArmond et al, 1995 ; Kellstein et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%